2023
DOI: 10.1039/d3ma00876b
|View full text |Cite
|
Sign up to set email alerts
|

Full-color emission of fluorinated benzothiadiazole-based D–A–D fluorophores and their bioimaging applications

Si-Hong Chen,
Xi-Ying Cao,
Peng-Tao Hu
et al.

Abstract: There is an active demand for full-color fluorophores in the field of fluorescent dyes. However, the core skeleton with simple structure and easy modification is currently insufficient. Herein, we developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…11–14 Through careful engineering of molecular structures and intermolecular interactions, researchers have achieved unprecedented control over emission wavelengths, intensity, and polarization in solid-state environments. 15–21 Numerous stator frameworks have been effectively employed to achieve solid-state fluorescence tunability in aggregation-induced emission luminogens (AIEgens). 23–31 In a study conducted by Zhang et al , these effects were demonstrated on the tetraphenylethene (TPE) scaffold through the strategic incorporation of donor and acceptor groups in the para position of the phenyl moieties, as well as the construction of push–pull systems (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…11–14 Through careful engineering of molecular structures and intermolecular interactions, researchers have achieved unprecedented control over emission wavelengths, intensity, and polarization in solid-state environments. 15–21 Numerous stator frameworks have been effectively employed to achieve solid-state fluorescence tunability in aggregation-induced emission luminogens (AIEgens). 23–31 In a study conducted by Zhang et al , these effects were demonstrated on the tetraphenylethene (TPE) scaffold through the strategic incorporation of donor and acceptor groups in the para position of the phenyl moieties, as well as the construction of push–pull systems (Fig.…”
Section: Introductionmentioning
confidence: 99%